2012
DOI: 10.1007/s00415-012-6440-7
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid levels predict survival in men with amyotrophic lateral sclerosis

Abstract: Elevated uric acid levels have recently been found to be associated with slower disease progression in Parkinson’s disease, Huntington’s disease, multiple system atrophy, and mild cognitive impairment. The aim of this study is to determine whether serum uric acid levels predict survival in amyotrophic lateral sclerosis (ALS). A total of 251 people with ALS enrolled in two multicenter clinical trials were included in our analysis. The main outcome measure was survival time, which was calculated as time to death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 22 publications
3
75
0
1
Order By: Relevance
“…4a). The list includes several features previously reported to predict ALS progression, including time from onset, age, forced vital capacity (FVC), site of onset, gender, weight [17][18][19][20] , as well as uric acid concentration in blood, a feature that has only been suggested recently as a predictor 20 . In addition, the challenge was successful in identifying nonstandard predictive features, opening the door to new insights into ALS disease mechanisms.…”
Section: Predictive Featuresmentioning
confidence: 99%
“…4a). The list includes several features previously reported to predict ALS progression, including time from onset, age, forced vital capacity (FVC), site of onset, gender, weight [17][18][19][20] , as well as uric acid concentration in blood, a feature that has only been suggested recently as a predictor 20 . In addition, the challenge was successful in identifying nonstandard predictive features, opening the door to new insights into ALS disease mechanisms.…”
Section: Predictive Featuresmentioning
confidence: 99%
“…Progression Inverse association [22][23][24] Inverse association [25][26][27][28] No association [29,30] Inverse association in HD, MSA, MCI [31][32][33] Laboratory…”
Section: Urate and Its Determinants Are A Risk Factor For Neurodegenementioning
confidence: 99%
“…Higher urate levels are associated with slower clinical progression in Huntington's disease, multiple system atrophy, and mild cognitive impairment [29][30][31]. In ALS, most [25][26][27][28] but not all [32,33] studies found urate to represent a prognostic factor for survival. The reasons for these conflicting results in ALS are not completely clear and may be related to methodological differences, variable sample size, and a modest effect size.…”
Section: Urate and Its Determinants Are Molecular Predictors Of Diseamentioning
confidence: 99%
“…Neurofilament light chain in cerebrospinal fluid (CSF) appears to increase as ALS progresses [19,[27][28][29][30][31]. Urate, which is lower in people with ALS than in controls, could serve a predictive or prognostic role [32][33][34][35][36]. Regulatory T cells, which are reduced in patients with rapidly progressive ALS, may be a predictive marker [37,38].…”
Section: Toward Novel Outcome Measures and Biomarkers In Als Trialsmentioning
confidence: 99%